Institutional Fundamentals of Communicative Relations of State Bodies and Society: Experience of Kazakhstan - Aryn, Е.М.; Aryn, Р.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
More than a quarter-century experience of state-building of an independent Kazakhstan has set its own ‘agenda’ for the modernization of both the institutions of state authorities and civil society, and the forms of their interaction. The young modern country at the very first steps of its formation faced with the range of problems in transition from quasi-state institutions of governance to the principles of a democratic, socially responsible, open civil society. Considering the above-mentioned issues, this scientific and analytical report presents a comprehensive analysis of the history and practice of the development of public communications with public institutions, including the experience of the Republic of Kazakhstan. In this regard, the purpose of the article is to assess the constructive experience of communication between the authorities and society; to consider country, social and political features of forming models of communication relations of the state; to determine the institutional bases of communication relations of various state authorities with the institutions of society in terms of their Kazakhstani experience in design and construction; to identify priority areas increasing the efficiency of the state’s communication functions and solving the systemic problems of their regulation in the materials of the Republic of Kazakhstan. This research proposes the statement that the specific findings and suggestions aim at the dynamization of communication links of state institutions and society at the present stage of development of the Republic of Kazakhstan.